Reviewing the Ecosystem Services, Societal Goods, and Benefits of Marine Protected Areas - Marcos, Concepción; Díaz, David; Fietz, Katharina; Forcada, Aitor; Ford, Amanda; García-Charton, José Antonio; Goñi, Raquel; Lenfant, Philippe; Mallol, Sandra; Mouillot, David; Pérez-Marcos, María; Puebla, Oscar; et al. (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) are globally important environmental management tools that provide protection from the effects of human exploitation and activities, supporting the conservation of marine biological diversity, habitats, ecosystems and the processes they host, as well as resources in a broad sense. Consequently, they are also expected to manage and enhance marine ecosystem services and material, non-material, consumptive and non-consumptive goods and benefits for humans. There is however certain confusion on what constitutes an ecosystem service, and it is not always easy to distinguish between them and societal benefits. The main nuance is that an ecosystem service is the aptitude an ecosystem has or develops naturally or as consequence of a management action, and that manifests through its own properties (productivity, diversity, stability, quality of its key parameters, etc.), while a societal benefit is the economic or other profitability (emotional, educational, scientific, etc.) that humans obtain from said service or quality. In this work, 268 publications, together with our own experiences in the different investigations carried out in the MPAs that are part of the BiodivERsA3-2015-21 RESERVEBENEFIT European project, have been selected, reviewed and discussed to analize the knowledge status of the expected ecosystem services of MPAs and the societal benefits derived from them, sometimes providing information on their evidence, when they exist. We define and classify the effects of protection, ecosystem services and societal benefits and elaborate a conceptual model of the cause-effect relationships between them.